Challenges of building entrepreneurial ecosystems in peripheral places. Issue 3 (2nd September 2019) - Xu, Zimu; Dobson, Stephen
Abstract : Purpose: The purpose of this paper is to investigate challenges of building entrepreneurial ecosystems in peripheral places. The entrepreneurial ecosystem concept is developing a rising popularity among both academics and policymakers in recent years where much of the attention has been put in major urban cities. However, on the way to achieve balanced growth and equity, peripheral places should not be neglected. Thus, this paper links literature on ecosystem with peripheral region studies in creating a conceptual framework of developing entrepreneurial ecosystems in peripheral places. Design/methodology/approach: The paper first reviews literature on entrepreneurial ecosystems and challenges that peripheral places facing in particular. Then, taking into consideration of literature from both fields, a conceptual framework is developed. In order to better illustrate the framework, a case study on Guildford's digital gaming industry is reviewed based on secondary data. Findings: Though facing various challenges such as smallness, remoteness and lack of resources, peripheral places can take advantage of the digital technology and build an entrepreneurial ecosystem of its own kind through holistic collaborative approach to tackle issues around finance, talents, socio-culture environment, infrastructure, markets and policy. Originality/value: The paper is among the first to focus on developing a holistic conceptual framework in building entrepreneurial ecosystems in peripheral areas. It can lead to a range of further research topics and contribute to develop viable practices particularly for policymakers.